2012
DOI: 10.1152/jn.00030.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor enhances the excitability of rat sensory neurons through activation of the atypical protein kinase C isoform, PKMζ

Abstract: Zhang YH, Kays J, Hodgdon KE, Sacktor TC, Nicol GD. Nerve growth factor enhances the excitability of rat sensory neurons through activation of the atypical protein kinase C isoform, PKM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 109 publications
5
55
0
Order By: Relevance
“…To date there has not been any characterization of PKC isoform expression in vagal sensory neurons, although PKC expression in somatosensory DRG neurons indicates that, at a minimum, b1, b2, d, «, and z are expressed in complex combinatorial patterns (Cesare et al, 1999;Wu et al, 2012). Similar to our findings, PKC has repeatedly been shown to play a role in inflammation-induced hyperexcitability in nociceptive DRG (Cesare et al, 1999;Baker, 2005;Wu et al, 2012;Zhang et al, 2012). It is known that PMA binds to the same enzyme subsite as DAG, and thus PMA activates only classic and novel PKC isoforms, suggesting that PKC expression is not limited to atypical isoforms in vagal sensory nerves.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…To date there has not been any characterization of PKC isoform expression in vagal sensory neurons, although PKC expression in somatosensory DRG neurons indicates that, at a minimum, b1, b2, d, «, and z are expressed in complex combinatorial patterns (Cesare et al, 1999;Wu et al, 2012). Similar to our findings, PKC has repeatedly been shown to play a role in inflammation-induced hyperexcitability in nociceptive DRG (Cesare et al, 1999;Baker, 2005;Wu et al, 2012;Zhang et al, 2012). It is known that PMA binds to the same enzyme subsite as DAG, and thus PMA activates only classic and novel PKC isoforms, suggesting that PKC expression is not limited to atypical isoforms in vagal sensory nerves.…”
supporting
confidence: 86%
“…Upon activation, PKC translocates to the plasma membrane, in which it engages in phosphorylation of a wide variety of protein targets. Given that previous studies demonstrated multiple isoforms of PKC heterogeneously expressed throughout the somatosensory DRG neuronal population (Cesare et al, 1999;Hayase et al, 2007;Wu et al, 2012;Zhang et al, 2012) and that PKC isoform expression has not yet been characterized in vagal neurons, we decided in this study to observe global PKC translocation using a pan-PKC antibody that would detect all PKC isoforms. All vagal neurons were immunoreactive for PKC with no fluorescent signal observed in the absence of primary antibody (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PKC not only acts as a second messenger but BDNF and NGF also modulate the activity of PKC [96,97]. PKC, in turn, influence the expression of NTFs, such as NGF [98], BDNF [99], and glial cell line-derived neurotrophic factor [100].…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%
“…The siRNA sequence targeting rat PKMζ, 5′-GCAAGCTGCTTGTCCATAAAC-3′, has been shown previously to efficiently downregulate rat PKMζ expression (50). Pairs of complementary oligonucleotides containing these sequences were synthesized and cloned into the pGMLV-SB1 lentivector.…”
Section: Lentiviral Shrna-mediated Knockdown Of Hippocampal Pkmζmentioning
confidence: 99%